The cytochrome b5 CybE is regulated by iron availability and is crucial for azole resistance in A. fumigatus. Issue 11 (26th October 2017) - Misslinger, Matthias; Gsaller, Fabio; Hortschansky, Peter; Müller, Christoph; Bracher, Franz; Bromley, Michael J.; Haas, Hubertus
Abstract : Cytochrome P450 enzymes (P450) play essential roles in redox metabolism in all domains of life including detoxification reactions and sterol biosynthesis. Abstract : Cytochrome P450 enzymes (P450) play essential roles in redox metabolism in all domains of life including detoxification reactions and sterol biosynthesis. The activity of P450s is fuelled by two electron-transferring mechanisms, heme-independent P450 reductase (CPR) and the heme-dependent cytochrome b 5 (CYB5)/cytochrome b 5 reductase (CB5R) system. In this study, we characterised the role and regulation of the cytochrome b 5 CybE in the fungal pathogen Aspergillus fumigatus . Deletion of the CybE encoding gene ( cybE ) caused a severe growth defect in two different A. fumigatus isolates, emphasising the importance of the CB5R system in this pathogen, while the non-essentiality of cybE indicates the partial redundancy of the CPR and CB5R systems. Interestingly, the growth defect caused by the cybE loss of function was even more drastic in A. fumigatus strain AfS77 compared to strain A1160P+ indicating a strain-dependent degree of compensation, which is supported by azole resistance studies. In agreement with CybE being important for the assistance of the ergosterol biosynthetic P450 Cyp51, deletion of cybE decreased resistance to the Cyp51-targeting antifungal voriconazole and caused accumulation of the ergosterol pathway intermediate eburicol. Northern analysis indicated that CybE deficiency leads to the compensatory transcriptional upregulation of Cyp51-encoding cyp51A and CPR-encoding cprA . Overexpression of cybE did not affect azole resistance suggesting that CybE activity is not rate limiting. Expression of cybE was found to be repressed during iron starvation by the iron-regulatory transcription factor HapX demonstrating iron dependence of CybE not only at the level of enzyme activity but also at the level of gene expression.